The role and place of the pharmacist-cosmetologist in the choosing and implementation of a cosmetology procedure for hair removal - N. O. Tkachenko; T. V. Mahanova; H. I. Makurina; N. V. Hrinivetska (Zaporozhye State Medical University, 2023)
In modern cosmetology, the issue of the availability of highly qualified specialists in accordance with the needs of the industry and the implementation of effective cosmetology procedures is acute, which actualizes research on the formation of a patient-centered model of providing medical and pharmaceutical assistance of aesthetic cosmetology. The aim of the work is to substantiate the role and place of the pharmacist-cosmetologist in the selection and provision of a cosmetology procedure for hair removal (CPHR) based on a conjoint analysis of consumer preferences for the specified service. Materials and methods. The main research material for this study included publications by both domestic and foreign scientists concerning aesthetic cosmetology services, consumer behavior regarding cosmetology procedures, professional competencies expected of a pharmacist-cosmetologist, as well as the results of a sociological survey conducted by the CPHR. The research methods employed in this study encompassed information search, synthesis, generalization, formalization, modeling, questionnaires, and regular conjoint analysis. Results. The most attractive methods of epilation were determined - electro epilation, elos epilation and laser epilation. It was established that the majority of consumers do not need a preliminary cosmetologist consultation, but want a consultation after. An algorithm for accompanying CPHR by a pharmacist-cosmetologist was developed. The relevant aspects of pharmaceutical care of CPHR were defined. Conclusions. The conducted conjoint analysis indicates that women are primarily focused on the effectiveness of CPHR (electro epilation, elos epilation, and laser epilation are considered the most effective) and its cost, and then - on the supporting component of the service. The specialist can offer the client (patient) the choice of a method and directly carry out the procedure, having knowledge and experience in diagnosing the condition of the skin and its appendages and understanding the specifics of CPHR against the background of the pharmacoeconomic analysis. The modern Ukrainian model of pharmacist-cosmetologist training allows marketing requirements and accompanying the customer at CPHR. Prospects for further research - formation of an information array and development of pharmaceutical care (assistance) protocols for a pharmacist-cosmetologist in various cosmetic procedures.